Health Problems in Schoolchildren Due to Backpacks: A Cross Sectional Study in Two Schools of a Town in North Karnataka - Ayesha Nawaz; Swetha Rajeshwari; Bheemayya Badesab (Medsci Publications, 2018)
Background: It is a common sight to see school children carrying a schoolbag on their backs that are too heavy for their body frames. Carrying heavy backpacks causes heavy load on the developing spine resulting in postural problems, back pain and discomfort. Objectives: The study was conducted to measure the schoolbag weight and its percentage to the bodyweight of schoolchildren and to study the health problems in schoolchildren due to heavy backpacks and factors influencing it. Methods: This cross sectional study was carried out in two schools for a period of two months among children studying in 7th to 10th standard. Children filled a pretested questionnaire and were weighed with and without schoolbag. Data was entered in MS Excel and analysed using Epi info7. Results: Out of 277 children 132 belonged to CBSE and 145to state syllabus, 68.6% children were carrying heavy backpacks.52.7% children complained of pain; majority had pain in leg, shoulder and back. CBSE students and those carrying loaded backpacks reported more pain. Conclusion: Children need to be taught packing bag the right way to avoid health problems.